(untitled) (Journal of Parents and Teachers, 1997)
The search for identity in young people is a central theme of the document, which highlights the crisis of knowledge and emotional insecurity they experience. The relevance of close relationships and the self-construction of their identity from diverse cultural influences is underlined. Despite the confusion, values of solidarity and belonging are maintained in their behavior.